PECS - picture exchange communication system with autism spectrum disorders - Nargiz Firdovsi Sultan (World Scientific Reports, 2026)
Picture exchange communication system (PECS), based on the principles of applied behavior analysis and based on normal language and communication development stages, it is an alternative illustrated communication system developed for individuals with ASD (Bondy & Frost, 2001; Charlop-Christy, Carpenter, Le, LeBlanc, & Kenneth, 2002; Kırcaali-İftar, 2007). PECS is used to teach individuals to communicate in a social context. Initially, using PECS, individuals are taught to give a picture (picture card) to a communication partner to retrieve the desired object (Wong, 2013b). Thus, individuals are enabled to initiate communication to achieve a goal. Studies carried out that PECS leads to an increase in imitation, communication and speaking skills and a decrease in problem behaviors (Bondy and Frost, 2001; Charlop-Christy et al., 2002). The PECS teaching process begins with teaching how to communicate using picture cards.